1999
DOI: 10.1097/00003246-199904000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ibuprofen on the physiology and survival of hypothermic sepsis

Abstract: Hypothermic sepsis has an incidence of approximately 10% and an untreated mortality twice that of severe sepsis presenting with fever. When compared with febrile patients, the hypothermic group has an amplified response with respect to cytokines TNF-alpha and IL-6 and lipid mediators TxB2 and prostacyclin. Treatment with ibuprofen may decrease mortality in this select group of septic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
121
3
13

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(142 citation statements)
references
References 24 publications
5
121
3
13
Order By: Relevance
“…Whereas the majority (ϳ90%) of patients with systemic inflammation have an increased T b , a number of them (ϳ10%) have a lowered T b (6,17). Thermoregulatory manifestations are also present in animal models of systemic inflammation.…”
mentioning
confidence: 99%
“…Whereas the majority (ϳ90%) of patients with systemic inflammation have an increased T b , a number of them (ϳ10%) have a lowered T b (6,17). Thermoregulatory manifestations are also present in animal models of systemic inflammation.…”
mentioning
confidence: 99%
“…Increase in mortality 28,51,52 CAD Increase incidence of vasopressor and/or inotropic support 11 Increase occurrence of arrhythmia 3 Increase rate of angina or myocardial ischemia 3,10 Increase in mortality 11 …”
Section: Sepsismentioning
confidence: 99%
“…Hypothermia has specifically been shown to be detrimental in patients with certain comorbidities as emphasized in Table 3. In septic patients, hypothermia is associated with a much higher incidence in mortality [28,51,52]. This is likely because fever--a form of autologous hyperthermia--functions as an immunologic defense that combats infection [28,[33][34][35].…”
Section: Traumamentioning
confidence: 99%
“…Moreover, several studies have shown that hypothermia delays the induction of proinflammatory cytokines in vitro (7). At the same time, however, several studies have reported that the mortality rate of hypothermic patients with sepsis is twice that of febrile septic patients (2,4,9). We studied the effects of hypothermia on mortality rate, concentrations of TNF-␣ and IL-6 in plasma, and the end products of NO in endotoxin-exposed rats.…”
mentioning
confidence: 97%